O efeito da estrutura familiar sobre o comportamento de risco à saúde em adolescentes no Brasil - Peñaloza, Rayén Heredia (2021)
The purpose of this study is to estimate the effect of family structure on the risky behavior of Brazilian adolescents and to analyze the effect according to the levels of education (elementary school and high school). This analysis uses data from the PeNSE (National Student’s Health Survey) of 2015 which provides information about health behaviors among 13 to 17 years old Brazilian students. The sample is subdivided in Elementary School and High School. Estimations were made using the propensity score matching method and the risky behaviors considered for the estimation were: consumption of alcohol, cigarettes, and illicit drugs. As covariates were used characteristics of the student and his family’s background. Brazilian adolescents from a single-parent family are more likely to smoke, to consume alcohol and illicit drugs when compared to those from two-parent families (an increase of 6.22% for cigarettes and alcohol, and 3.82% for illicit drugs). Thus, the results suggest that being raised in a disruptive family has negatively affects the health risk behavior of adolescents when analyzed by the issue of substance use, mainly when it comes to the consumption of alcohol and cigarettes. Furthermore, we observed an increase of the frequency of substance used by age of the adolescents.